Majalah DABIQ Sebagai Medium Propaganda Pemikiran Tauhid Islamic State of Iraq and Sham (ISIS): DABIQ Magazine as Medium of Propagation for Thought of Tawhid by Islamic State of Iraq and Sham (ISIS) - Wahab, Muhammad Rashidi; Hamat, Mohd Fauzi; Hanafiah, Mohd Hizam; Muhammad Uthman El-Muhammady, Ahmad El-Muhammady; Jalil, Abdullaah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
Extremism is an emerging threat confronted by the Muslim world today manifested in the form of a group such as the Islamic State of Iraq and Syria (ISIS) or al-Dawlah al-Islamiyyah fi al-‘Iraq wa al-Sham (DAESH). Undoubtedly, the existence of ISIS and its violence gave negative impacts on Islam and the Muslim ummah worldwide. What is more concerning is that some Muslims in Malaysia were also influenced by ISIS and by so doing it poses threat to our national security. Thus, based on the textual analysis of ISIS document, this article seeks to examine the discourse of tawhid advocated by ISIS, considering the fact that every act committed by Muslims is usually rooted in his or her belief system. To do this, this article focuses on the discourse of tawhid as discussed in DABIQ magazine and it is chosen due to its significance since it is regarded as ISIS mouthpiece to spread its propaganda. Based on the analysis, the article identifies five key elements that constitute ISIS discourse of tawhid, namely (i) the ideological strand of Salafi-Wahabi, (ii) three divisions of tawhid, (iii) tawhid al-Wala’ wa al-Bara’, (iv) tawhid al-Hakimiyyah, and (v) takfirism. The analysis also concludes that ISIS tawhid is not consistent with the mainstream framework of Ahl al-Sunnah wa al-Jama‘ah and thus it should be repudiated.